Preoperative Alpha-Fetoprotein Slope is Predictive of Hepatocellular Carcinoma Recurrence after Liver Transplantation - Kathy Han; George N Tzimas; Jeffrey S Barkun; Peter Metrakos; Jean I Tchervenkov; Nir Hilzenrat; Phil Wong; M Deschênes (Canadian Journal of Gastroenterology)
BACKGROUND: Liver transplantation (LT) offers a possible cure for patients with hepatocellular carcinoma (HCC) and cirrhosis. However, tumour progression while on the waiting list and tumour recurrence after LT are common. The prognostic significance of various pre- and postoperative variables were investigated in regard to tumour recurrence, with an emphasis on the slope of preoperative serum alpha-fetoprotein (AFP) levels.